Analisis Perspektif Psikologi Tokoh Silas Marner dalam Novel Silas Marner Karya George Eliot - Heni (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2020)
A literary work is a form of the author's imagination written with a background in various fields of life. The characters in a literary story also have the same problems as humans in real life. The author, in writing a story, is motivated by the conditions and environment that exist around him and affects him. The story in a novel, short story, or poetry reflects various aspects of human life. Literary works will present a story that can be viewed from various points of view, including from a psychological perspective. We can examine each character from a psychological point of view. How the character's psychological condition will appear from a story that can be examined by looking at the character's behavior, how he relates to other characters, and how he deals with problems in his life. George Eliot's Silas Marner novel is an interesting story which can be examined from a psychological point of view, namely the psychology of existentialism. Silas Marner's character in this novel will be analyzed from a psychological perspective. How Silas Marner's character in self-existence will appear in the psychology of existentialism.